Enhancement of above ceiling space for utilization: /b single storey terrace house in Malaysia - Azuan Aziz Awang (School of Environmental Engineering, University Malaysia Perlis, 2012)
Use of ceiling space or attic, has a lot of increase in foreign countries but not in Malaysia, probably because the weather in Malaysia is equatorial climates where rain and warm throughout the year. This research made is to develop a method by using timber component and recommend roof-ceiling space for general utilization with minimal cost for single storey house in Malaysia. To determine whether the use of ceiling space can be increased or not, the questionnaires were distributed and there were 64 respondents who answered the question where the respondents obtained from six of the different resident areas around Perlis. There are 62 out of 64 respondents agreed that if the ceiling space usage can be improved in Malaysia. To determine the estimated cost of attic construction, the price of materials relating to the attic is collected and the cost of materials is calculated based on current prices obtained from the hardware around Perlis. Structure truss to be designed and determined whether it is stable or unstable before the calculation of the cost is made to avoid collapse or fail. Through the calculations made, the total cost of materials for the construction of the attic is RM 18774.7 while the total cost of materials for the construction of the normal roof is the RM 6386.15, The attic space is obtained by 13.38 mp2s where the volume of attic is 97.41 mp3s where the length of attic is 4.46 m, height is 3 m and the width of attic is 7.28 m. Can be concluded that the total cost of the attic construction is the reasonable cost in Malaysia.